A case of a fifteen-year-old patient suffering from rare adenocystic lung carcinoma bronchoplastic surgery - D. A. Kharagezov; E. A. Mirzoyan; Yu. Yu. Kozel; G. A. Mkrtchyan; A. A. Antonyan; T. G. Ayrapetova; I. A. Leyman; A. G. Milakin; O. N. Stateshny (Южно-Российский онкологический журнал, 2024)
Adenoid cystic carcinoma of the lung is a relatively rare malignant tumor, accounting for 0.04–0.2 % of all primary malignant tumors of the respiratory system. This carcinoma can occur at any age, but it is more common in the 40–60 age group and usually in women. The main treatment method for adenoid cystic carcinoma is surgical. Since tumors of this histological form are often centrally located, options for bronchoplastic operations are considered. In childhood, adenoid cystic carcinoma is extremely rare, and performing bronchoplastic lobectomies in children is associated with several difficulties, such as the smaller diameter of the bronchi compared to adult patients, complicating surgical intervention and subsequent rehabilitation. This clinical case demonstrates the experience of performing a bronchoplastic operation on a 15-year-old patient at the Department of Thoracic Oncology of the National Medical Research Centre for Oncology, Rostov-on-Don, Russian Federation. The patient was hospitalized complaining of prolonged cough, shortness of breath, and chest pain. Adenoid cystic carcinoma of the central type was identified during diagnostics, which included bronchoscopy, computed tomography, and biopsy. The surgical intervention involved performing a bronchoplastic lobectomy, during which the affected lobe of the lung was removed with resection and reconstruction of the bronchus. The operation was performed taking into account the anatomical features of the child's body, which required high precision and surgical skills. The postoperative period proceeded without significant complications, and the patient was under the supervision of a multidisciplinary team of specialists.This clinical case provides a detailed description of the results of preoperative diagnostic measures, the stages of the operation, and the postoperative follow-up results. Special attention was paid to the difficulties associated with the small diameter of the bronchi in children, which required the use of specialized instruments and techniques. The importance of using modern diagnostic and treatment methods, as well as close interdisciplinary interaction, is emphasized for a successful treatment outcome.The experience of performing such operations in childhood is extremely important for improving the quality and safety of surgical treatment of adenoid cystic carcinoma and other rare tumors in children. Further observations will be described in stages.